Voicing modes : a chord-voicing approach to hearing and practicing modes : for comping, improvisation, reharmonization & composition - Johnston, Noel (Noel Johnston, 2016)
"Voicing Modes is a book for all guitar players who want to master their modal comprehension and ability. Focuses on a chord-voicing approach to hearing and practicing modes. For comping, improvisation, reharmonization & composition. With detailed explanations, reference material, tune examples, and 8 modal etudes."--Author's website.